MR Lymphangiography in Pediatrics: Indications, Technique, Findings, and Management - Pimpalwar, Sheena; Hussain, Tarique; Reddy, Surendranath R. Veeram (Seminars in Interventional Radiology, 2025)
Over the past two decades, magnetic resonance imaging (MRI) has become the mainstay for lymphatic imaging in pediatric patients suffering from lymphatic disorders caused by congenital or acquired causes. Pediatric patients, especially those born with complex congenital heart disease, status post single ventricle palliation increasingly constitute the largest group of patients presenting with lymphatic dysfunction. Heavily T2-weighted and 3D-balanced steady-state free precession are complementary MRI sequences used for noninvasive assessment of the central lymphatic anatomy as well as distribution of lymphatic fluid in body cavities, lymphatic cysts, and lymphatic malformations. These sequences are, however, limited in their ability to visualize smaller lymphatics, to differentiate lymphatics from other fluid-filled structures, or to provide sequential flow information. This limitation is overcome by administering a gadolinium-based contrast agent into a lymph node, lymphatic vessel, or interstitial tissue with simultaneous image acquisition, a technique called dynamic contrast-enhanced magnetic resonance lymphangiography. This imaging is invasive but critical for evaluating lymphatic flow and identifying potential targets for lymphatic intervention. Medical therapy, along with traditional transcatheter or surgical approaches to address the underlying cause of the lymphatic disorder, remains the first-line approach, while lymphatic interventions are reserved for patients who have failed these therapies.
Keywords: dynamic contrast-enhanced MR lymphangiography; chylothorax; plastic bronchitis; chylous ascites; protein-losing enteropathy; interventional radiology